Profiles of sulfonylurea use in Diabetes Mellitus type 2: an analysis of clinical practice over the last 10 years - Baccetti, Fabio; Crisafulli, Cristiano; Andreozzi, Francesco; Mannino, Gaia Chiara; Nicolucci, Antonio; Michelli, Andrea; Miranda, Cesare; Candido, Riccardo; Di Bartolo, Paolo; Di Cianni, Graziano; Russo, Giuseppina Tiziana; Mannino, Domenico (Diabetes research and clinical practice, 2024)
Describing the evolution over time in the use of sulfonylureas (SUs) and the characteristics of patients at first prescription and at interruption of treatment with SUs. Retrospective evaluation of data from the Italian Association of Diabetologists (AMD) Annals registry (2010–2020), about T2D patients who started treatment with SUs. The longitudinal probability of remaining on SUs was estimated by Kaplan Meier survival curves. SU prescription decreased from 30.7 % (2010) to 12.9 % (2020). Patients started on SU were 68.2 ± 11.2 years old, mostly males (55.5 %), with diabetes duration = 10.1 ± 8.3 years, BMI = 29.7 ± 5.5 kg/m2, and HbA1c = 8.3 ± 1.7 % [67 mmol/mol]. After one year, the probability of staying on SU was 85.4 %, 75.9 % after two years, 68.2 % after 3 years, 56.6 % after 5 years. Patients who discontinued SUs had higher BMI and HbA1c, were younger, more often males and treated with insulin. Over time, the percentage of subjects switched to metformin, DPP4i, SGLT2i, and GLP1RA increased, whereas use of glinides, glitazones, acarbose and insulin declined. These data suggest a consensus, slowly, but increasingly aligning with the current National indications of dismissing SUs for the treatment of T2D. The new drugs for diabetes should represent a preferable choice in all patients who do not have specific contraindications.